2023
DOI: 10.7717/peerj.15065
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and distinguishing between apicultural plants using UAV multispectral imaging

Abstract: Detecting and distinguishing apicultural plants are important elements of the evaluation and quantification of potential honey production worldwide. Today, remote sensing can provide accurate plant distribution maps using rapid and efficient techniques. In the present study, a five-band multispectral unmanned aerial vehicle (UAV) was used in an established beekeeping area on Lemnos Island, Greece, for the collection of high-resolution images from three areas where Thymus capitatus and Sarcopoterium spinosum ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The existing literature has demonstrated that combining SAR and optical data allows for the identification of different physical and spectral characteristics of land cover, potentially enhancing classification outcomes [48,[66][67][68][69][70]. Moreover, the use of spectral indices has been shown to improve classification [48,[71][72][73].…”
Section: Methodsmentioning
confidence: 99%
“…The existing literature has demonstrated that combining SAR and optical data allows for the identification of different physical and spectral characteristics of land cover, potentially enhancing classification outcomes [48,[66][67][68][69][70]. Moreover, the use of spectral indices has been shown to improve classification [48,[71][72][73].…”
Section: Methodsmentioning
confidence: 99%
“…Interesting observations about detecting and distinguishing apicultural plants Thymus capitatus and Sarcopoterium spinosum, using UAV, were made in [26], whose training method distinguished the two plants with 70% accuracy. The optimal flight parameters and processing options for the detection of taxus and olive trees with UAV-Borne Imager are presented in [27].…”
Section: Introductionmentioning
confidence: 99%